Spinal Taenia solium cysticercosis in Mexican and Indian patients: a comparison of 30-year experience in two neurological referral centers and review of literature - Cardenas, Graciela (2016)
To present a retrospective study from patients with spinal cysticercosis (SC), diagnosed within the last 30 years in Mexican and Indian neurological referral centers. This is a retrospective and comparative study of the clinical and radiological profile between Mexican and Indian patients with spinal neurocysticercosis during a 30-year period and a review of the literature during the same period. Twenty-seven SC patients were included: 19 from Mexico and 8 from India. SC presented predominantly with motor symptoms (21/27 patients): paraparesis and paraplegia were the most common signs; one-third of patients presented sphincter dysfunction. Imaging studies showed that parasites in vesicular stage were more frequent in patients from Mexico, while degenerative stages predominated in India. Association of subarachnoid cysticerci and hydrocephalus was observed only in Mexican patients. Despite the limitations of this study, the collected information supports the existence of differences in the clinical and radiological traits of SC patients between Asian and Latin-American hospitals. The possible biological factors that may underlie these differences are discussed.